Influencia de las técnicas de modelado "Servicio Amigable" y "Plan Anfitrión" en el desempeño del personal operativo de la empresa PECSA Trujillo. - Vigo Polo, Bertha Rosa (2012)
This work is the research question How do the Modeling Techniques "Friendly Service" and "Host Plan" in the performance of our operational staff PECSA Trujillo? Given the hypothesis that the modeling techniques favorably influence the performance of our operational staff PECSA Trujillo. Which was taken to a population consisting of 5 service stations own the company, with a number of 54 workers, as shown using the same population to be this small and accessible. We used a research design based on a Pre experimental case study with a single measurement. As data collection instrument used a survey that was applied to all staff, with the aim of determining the level of knowledge, the level of acceptance of these techniques and their level of readiness to fulfill the customer steps, after application of modeling techniques. It was also used for performance measurement, monthly performance evaluations boxes outsourced by a company, called Hidden Client Assessment. It was concluded that these techniques ensured that operational staff have a better level of knowledge about basic concepts and description of each technique, internalizing what is the main purpose of this form of teaching. It was determined that the level of acceptance of these techniques was very good and satisfactory, with the consequence that their level of readiness so that they properly meet the customer steps is optimal, favorably influencing the performance of operating personnel. It was recommended that the company should continue to implement different types of learning techniques that are feasible to implement the operational staff, but is always focused on its main goal which is the Service Excellence, and performance measurement as performed by at least twice a month for greater monitoring and feedback and motivational programs also implemented staff to obtain their real commitment to the company that gives better performance as a result.